Peran, Tantangan dan Stratedi Pusat Penjaminan Mutu di Perguruan Tinggi Islam di Indonesia - Sul Pratama Putra; Moh. Juharis; Muhammad Ramli; Mardhiah Mardhiah (Institusi Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to examine the role, challenges, and strategies of Quality Assurance Centers in Islamic Higher Education Institutions. Using a qualitative descriptive method, the research explores how internal and external quality assurance systems are implemented to improve educational standards. Data were analyzed through document studies and literature reviews relevant to the quality assurance framework in higher education. The findings show that Quality Assurance Centers play a strategic role in ensuring academic, managerial, and ethical standards in line with Islamic values. However, various challenges arise, such as limited human resources, lack of commitment, and misalignment of regulations. To overcome these obstacles, strategic efforts are required, including strengthening internal systems, promoting a culture of quality, leveraging information technology, and enhancing governance and collaboration among stakeholders. The study concludes that the success of quality assurance in Islamic universities depends on consistent implementation, strong leadership, and stakeholder involvement to ensure sustainable improvement in educational quality.